2020
DOI: 10.1021/acsami.0c01527
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Sorbents for 129I Capture from Contaminated Groundwater

Abstract: Radioiodine (129I) poses a risk to the environment due to its long half-life, toxicity, and mobility. It is found at the U.S. Department of Energy Hanford Site due to legacy releases of nuclear wastes to the subsurface where 129I is predominantly present as iodate (IO3 –). To date, a cost-effective and scalable cleanup technology for 129I has not been identified, with hydraulic containment implemented as the remedial approach. Here, novel high-performing sorbents for 129I remediation with the capacity to reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 34 publications
(72 reference statements)
1
34
1
Order By: Relevance
“…It should be noted that the data presented in Table 2 should not be considered the sole determining factor in terms of the desired favourable interactions with aqueous iodine. For example, Fe oxyhydroxides have recently been identified as having potential in this remit and cerium has been used historically for iodate immobilisation [35].…”
Section: Metals For Iodine Capturementioning
confidence: 99%
See 4 more Smart Citations
“…It should be noted that the data presented in Table 2 should not be considered the sole determining factor in terms of the desired favourable interactions with aqueous iodine. For example, Fe oxyhydroxides have recently been identified as having potential in this remit and cerium has been used historically for iodate immobilisation [35].…”
Section: Metals For Iodine Capturementioning
confidence: 99%
“…Further recent research has demonstrated a different loading technique, in which the commercial resins were treated with an acidic solution of metal ions, followed by NaOH. This caused precipitation of metal oxides upon the adsorbent surface, creating a true hybrid material [35]. Some less common metals were trialled, including Bi, Ce and Fe, with a CeO 2 -loaded resin proving the most efficient material.…”
Section: Ion-exchange Resinsmentioning
confidence: 99%
See 3 more Smart Citations